Water-redispersible polymer powders for dry building material formulations
By using alkali metal sulfate or alkali metal sulfite as drying additives in the production of polymer powder, the problem of reducing tensile adhesion strength of building products after thermal aging is solved, and the effect of significantly improving this characteristic when using a small amount of polymer powder is achieved.
Patent Information
- Application Number
- CN202380064022.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-15
AI Technical Summary
The tensile adhesion strength of existing polymer powders decreases after thermal aging of construction products, especially when used in climate change and warmer countries, this property needs to be further improved, especially when using small amounts of polymer powder.
The polymer powder is produced by using alkali metal sulfate or alkali metal sulfite as a drying aid, and the proportion of alkali metal sulfate or alkali metal sulfite in the total weight of the drying aid is ≥25%, and the proportion of water-soluble organic polymer is ≤40%.
The tensile adhesion strength of building products after thermal aging is significantly improved, and significant results can be achieved even with relatively small amounts of polymer powder.
Smart Images

Figure BDA0005298778570000211 
Figure BDA0005298778570000221
Abstract
Description
Technical Field
[0001] The present invention relates to a process for producing polymers in the form of water-redispersible powders by adding alkali metal sulfates or alkali metal sulfites, to the polymer powders obtainable thereby, and to their use, for example, in dry formulations of building materials such as tile adhesives, sealing slurries, self-leveling compositions or reinforcing compositions. Background Art
[0002] As is known, a polymer in the form of a water-redispersible powder (polymer powder) refers to a powder composition obtainable by drying a corresponding aqueous polymer dispersion in the presence of a drying aid. This production process results in the finely dispersed polymer resin in the dispersion becoming covered with a generally water-soluble drying aid. During the drying process, the drying aid acts as a jacket to prevent the particles from irreversibly sticking together. When the polymer powder is redispersed in water, the drying aid dissolves and an aqueous redispersion is formed, in which the original polymer particles (polymer primary particles) are present again as much as possible (Schulze J. in TIZ, No. 9, 1985).
[0003] In the search for providing polymer powders with such redispersible properties, progress has been made in the past in a number of different directions and a number of different drying aids have been discovered, in particular water-soluble organic polymers. Thus, for example, US5567750 teaches polyvinyl alcohol as a drying aid. US5874524 recommends polyelectrolytes for this purpose and EP0078449 vinylpyrrolidone-vinyl acetate polymers or alkali metal or alkaline earth metal salts of naphthalenesulfonic acid-formaldehyde condensates. Such naphthalenesulfonic acid-formaldehyde condensates are also disclosed in EP407889. Starch (derivatives) have also been used many times as drying aids, as described in EP134451.
[0004] Polymer powders are widely used as additives for dry formulations of building materials based on hydraulically setting binders, especially cement, and also as fillers and additives as described in US2007037925, for example as tile adhesives, joint fillers, spackling compounds, sealing slurries, plasters or screeds. The addition of polymer powders to dry formulations of building materials makes it possible, for example, to improve the cohesive or adhesive properties of the hardened building products, in particular their mechanical strength, such as tensile adhesion strength.
[0005] However, the tensile adhesion strength of building products is reduced by the action of heat. Solar radiation and underfloor heating expose building products to thermal stresses, which lead to mechanical stresses in the building products and weaken the tensile adhesion strength of the building products. Building products need to withstand such thermal stresses throughout their service life (spanning many years). The tensile adhesion strength of building products after thermal aging is an important measure of their resistance to thermal stresses. Although improvements in tensile adhesion strength after thermal aging can be achieved using standard polymer powders, against the background of climate change and the use of polymer-modified building material formulations in warmer countries, there is a need to further improve the tensile adhesion strength after thermal aging and to achieve this in the most efficient way possible, especially when only small amounts of polymer powders are used. Summary of the invention
[0006] In this context, the aim is to improve the tensile adhesion strength of building products after heat aging. This should preferably be achieved in the most efficient way possible, especially when only small amounts of polymer powder are used.
[0007] Surprisingly, this object was achieved by producing the polymer powder using alkali metal sulfates or alkali metal sulfites as drying aids alone or in significant proportions and producing the polymer powder using ≤40% by weight of water-soluble organic polymer as drying aid, based on the total weight of the water-soluble organic polymer and protective colloid. This was particularly surprising since the water-soluble organic polymers established to date as drying aids also have binder properties that have a positive influence on tensile adhesion strength, whereas the invention uses at least a portion of alkali metal sulfates or alkali metal sulfites as drying aids, which are not known per se to be able to improve the tensile adhesion strength of building products after thermal aging.
[0008] WO21239234 improves the storage stability of polymer powders by adding alkali metal sulfates or magnesium sulfate, but uses established water-soluble organic polymers as drying aids in conventional amounts. US2007037925 has the object of providing a mortar with accelerated setting and teaches for this purpose the addition of a polymer powder composition modified with an alkali metal salt or alkaline earth metal salt of an inorganic or organic acid. Here too, conventional water-soluble organic polymers are used as drying aids in conventional amounts. WO2017 / 178422 discloses an aqueous polymer dispersion comprising a drying aid and a water-soluble salt a of a polyvalent metal such as an alkaline earth metal, aluminum, zirconium, iron or zinc, and another water-soluble salt b of an anion such as aluminate, silicate, borate, sulfate or carbonate, wherein the polyvalent metal of salt a) forms a water-insoluble salt with the anion of salt b), and subsequent drying produces a water-insoluble salt formed by salt a) and b), forming a shell on the polymer particles that dissolves only in an alkaline medium or due to mechanical stress. Based on the polymer core, the proportion of the inorganic shell is 10% to 50% by weight or 10% to 20% by weight. The water-insoluble salt shell hinders the agglomeration of the polymer particles and acts as an anti-caking agent.
[0009] The polymerization of ethylenically unsaturated monomers is usually initiated by an initiator, such as an alkali metal persulfate. As is known, the initiator decomposes into free radicals, which add to the ethylenically unsaturated monomers, thereby initiating polymer chain growth. The initiator is thus covalently linked to the polymer formed during the polymerization process, so that the initiator is not present in the polymer dispersion in the form of an inorganic low molecular weight compound, such as an alkali metal sulfate, or is present only in an insignificant amount.
[0010] The present invention provides a process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders (polymer powders).
[0011] The method is carried out by drying an aqueous dispersion of a protective colloid-stabilized polymer based on ethylenically unsaturated monomers (polymer dispersion) in the presence of one or more drying aids, characterized in that
[0012] The drying aid comprises a) one or more inorganic salts selected from the group of alkali metal sulfates and alkali metal sulfites and b) optionally one or more water-soluble organic polymers, and
[0013] After all the drying aid has been added, the inorganic salt a) is present in dissolved form in the polymer dispersion,
[0014] wherein the inorganic salt a) is used as a drying aid in an amount of ≥ 25% by weight, based on the total weight of the drying aid, and
[0015] Therein, the proportion of any water-soluble organic polymer b) used as drying aid is ≤40% by weight, based on the total weight of the protective colloid and any water-soluble organic polymer b) used as drying aid.
[0016] The present invention further provides protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders (polymer powders) obtainable by the above-described process according to the invention.
[0017] The inorganic salt a) used as a drying aid is preferably selected from the group consisting of lithium sulfate (Li 2 SO 4 ), sodium sulfate (Na 2 SO 4 ), potassium sulfate (K 2 SO 4 ), lithium sulfite (Li 2 SO 3 ), sodium sulfite (Na 2 SO 3 ), and potassium sulfite (K 2 SO 3 ). Particularly preferred are sodium sulfate, sodium sulfite, potassium sulfate, and potassium sulfite. Most preferred are sodium sulfate and sodium sulfite. Sulfate is more preferred herein.
[0018] After all the drying aids have been added, the inorganic salt a) is present in dissolved form in the polymer dispersion. Preferably, after the total amount of all drying aids has been added, the inorganic salt a) is present in dissolved form in the polymer dispersion. Before drying and / or at the beginning of drying, the inorganic salt a) is usually present in dissolved form in the polymer dispersion. However, this does not exclude that part of the inorganic salt a) is present in the polymer dispersion in an undissolved form, for example adhering to the components of the polymer dispersion. Preferably, at least a major part of the inorganic salt a) is present in dissolved form in the polymer dispersion. More preferably, based on the total weight of the inorganic salt a) introduced into the polymer dispersion as a drying aid,>50% by weight, even more preferably>70% by weight, particularly preferably>90% by weight, and most preferably>99% by weight of the inorganic salt a) is present in dissolved form in the polymer dispersion. Most preferably, the inorganic salt a) introduced as a drying aid is completely present in dissolved form in the polymer dispersion. All this generally also applies to the case where, in addition to the inorganic salts a), there are further organic or in particular inorganic salts introduced into the polymer dispersion or present in the polymer dispersion. When two or more inorganic salts a) are introduced into the polymer dispersion, these generally do not lead to the formation of insoluble salts.
[0019] The measure and method according to the invention for determining the solubility of inorganic salts a) in polymer dispersions is their solubility in water. The inorganic salts a) or, when further organic or especially inorganic salts are used, their mixtures with the inorganic salts a) have a water solubility of preferably ≥1 g / liter of water, more preferably ≥3 g / liter of water, even more preferably ≥10 g / liter of water, particularly preferably ≥50 g / liter of water, and most preferably ≥100 g / liter of water, in each case under standard conditions according to DIN 50014 (23° C. / 50% relative humidity). These values preferably relate to a neutral pH value, i.e. pH 7.
[0020] The polymer dispersion and / or polymer powder preferably comprises from 0.1 to 20% by weight, more preferably from 0.2 to 10% by weight, even more preferably from 0.3 to 5% by weight, even more preferably from 0.4 to 4% by weight, particularly preferably from 0.5 to 3%, most preferably from 1 to 2% by weight and most preferably from 1.1 to 2% by weight of inorganic salt a), based on the total weight of the polymer based on ethylenically unsaturated monomers.
[0021] The proportion of the inorganic salt a) is preferably 2 to 50% by weight, more preferably 3 to 30% by weight and most preferably 5 to 20% by weight, based on the total weight of the protective colloid.
[0022] The proportion of inorganic salt a) is preferably 2 to 50% by weight, more preferably 3 to 30% by weight and most preferably 5 to 20% by weight, based on the total weight of protective colloid and water-soluble organic polymer b).
[0023] The proportion of the inorganic salt a) is preferably >25% by weight, more preferably ≥30% by weight, even more preferably ≥40% by weight, even more preferably ≥50% by weight, even more preferably ≥60% by weight and particularly preferably ≥80% by weight, based on the total weight of the drying aid.
[0024] Most preferably, only inorganic salts a) are used as drying aids.
[0025] The above-mentioned % values by weight for the amount of inorganic salt a) according to the invention are preferably based on the proportion of inorganic salt a) present in dissolved form in the polymer dispersion when the polymer dispersion contains salts (especially cations) which form water-insoluble salts with anions (especially sulfate) of the inorganic salt a). This is particularly preferred when the polymer dispersion contains cations of alkaline earth metals, aluminum, zirconium, iron or zinc.
[0026] The water-soluble organic polymers b) used as drying aids have a water solubility of preferably ≥1 g / liter of water, more preferably ≥3 g / liter of water and most preferably ≥10 g / liter of water, in each case under standard conditions (23° C. / 50% relative humidity) according to DIN 50014. These values preferably relate to a neutral pH value, i.e. pH 7.
[0027] Examples of water-soluble organic polymers b) suitable as drying aids are polyvinyl alcohol, polyvinyl acetal, nonionic polyvinyl pyrrolidone, nonionic poly(meth)acrylamide, polysaccharides and proteins. The water-soluble organic polymer b) is obtainable by methods known to those skilled in the art. Preference is given herein to nonionic water-soluble organic polymers b). Nonionic water-soluble organic polymers b), especially nonionic polyvinyl pyrrolidone and nonionic poly(meth)acrylamide, usually do not contain any ionic monomer units and usually do not carry any ionic groups, especially ammonium, carboxylic acid or sulfonic acid groups. Nonionic polyvinyl pyrrolidone is preferably composed of vinyl pyrrolidone units. Nonionic poly(meth)acrylamide is preferably composed of (meth)acrylamide units.
[0028] More preferred are polyvinyl alcohol; polyvinyl acetals; polysaccharides, especially water-soluble forms, such as starch (amylose and amylopectin), cellulose or its derivatives, such as carboxymethyl, methyl, hydroxyethyl or hydroxypropyl derivatives; and proteins, such as casein or caseinates, soy protein and gelatin. Particularly preferred is polyvinyl alcohol. Most preferably, no further water-soluble organic polymers b) are used as drying aids in addition to polyvinyl alcohol.
[0029] Preferred polyvinyl alcohols are partially or fully hydrolyzed polyvinyl alcohols having a degree of hydrolysis of preferably 80 to 100 mol %. Particularly preferred are partially hydrolyzed polyvinyl alcohols having a degree of hydrolysis of 80 to 95 mol %, in particular having a hydrolysis rate of 1 to 30 mPa·s in a 4% aqueous solution. Viscosity (at 20°C) Most preferred are polyvinyl alcohols having a degree of hydrolysis of 85 to 94 mol %, in particular those having a hydrolysis rate of 3 to 15 mPa·s in a 4% aqueous solution. Viscosity (at 20°C) method, DIN 53015).
[0030] The polymer dispersion and / or polymer powder preferably comprises ≤15% by weight, more preferably ≤10% by weight, even more preferably ≤5% by weight, even more preferably ≤3% by weight, particularly preferably ≤0.9% and very particularly preferably ≤0.5% by weight of water-soluble organic polymer b) as drying aid, based on the total weight of the polymer based on ethylenically unsaturated monomers.
[0031] The polymer dispersion and / or polymer powder comprises preferably <40% by weight, more preferably ≤30% by weight, even more preferably ≤20% by weight, even more preferably ≤10% by weight, particularly preferably ≤5% and most preferably ≤1% by weight of water-soluble organic polymer b) as drying aid, based on the total weight of the protective colloid.
[0032] The polymer dispersion and / or polymer powder comprises preferably <40% by weight, more preferably ≤30% by weight, even more preferably ≤20% by weight, even more preferably ≤10% by weight, particularly preferably ≤5% and most preferably ≤1% by weight of water-soluble organic polymer b) as drying aid, based on the total weight of protective colloid and any water-soluble organic polymer b).
[0033] The proportion of water-soluble organic polymers b) as drying aids is preferably ≤70% by weight, more preferably ≤50% by weight, even more preferably ≤30% by weight, particularly preferably ≤10% by weight, very particularly preferably ≤5% by weight, based on the total weight of the drying aid.
[0034] Most preferably of all, no water-soluble organic polymers b) are used as drying aids.
[0035] Any water-soluble organic polymer b) used as drying aid is usually added to the polymer dispersion, i.e. usually after the production of the polymer dispersion by polymerization. Therefore, the water-soluble organic polymer b) used as drying aid is usually used after the end of the polymerization). As is known, the end of polymerization is perceptible, for example, by a decrease in the heat release by the polymerization batch. After the end of the polymerization, the polymerization batch usually no longer releases heat. Therefore, ethylenically unsaturated monomers, protective colloids or initiators are usually not added to the polymer dispersion after the production of the polymer dispersion by polymerization. Therefore, the addition of the water-soluble organic polymer b) used as drying aid takes place in particular after the polymerization batch has been degassed or excess pressure has been released therefrom, or after post-polymerization, or after the removal of residual monomers, or preferably after the completion of the polymer dispersion, i.e. after the addition of additives such as preservatives or defoamers.
[0036] On the other hand, as is known, the protective colloid is usually present during the polymerization. Thus, the addition of the protective colloid usually takes place before or during the polymerization, or before or during the addition of the monomers or initiators, especially before the addition of the monomers or initiators is complete. Thus, the addition of the protective colloid usually also takes place before the removal of residual monomers, or before the post-polymerization, i.e., usually before the end of the polymerization.
[0037] These process steps are inevitably reflected in the structural properties of the polymer powder. For example, as is known, protective colloids and water-soluble organic polymers b) used as drying aids are usually incorporated into the polymer powder in completely different ways and fulfill completely different functions, and therefore, differences in the type or mode of addition of protective colloids and drying aids lead to differences in the process and in the material properties of the polymer powder.
[0038] Thus, during polymerization in an aqueous medium, the protective colloid generally stabilizes the polymerization batch and also stabilizes the polymer particles formed during the polymerization. The polymer particles formed during the polymerization are also referred to as primary particles. The protective colloid is generally incorporated into the primary particles or physically or chemically bound to the primary particles, preferably irreversibly, for example by physical entanglement or by covalent bonding, or by polymer encapsulation formed during the polymerization.
[0039] On the other hand, the water-soluble organic polymer b) used as a drying aid is usually not incorporated into the primary particles. After polymerization, the addition of the water-soluble organic polymer b) used as a drying aid usually causes the primary particles to be encased (encase, embedded) therein. The powdery particles formed during drying are also referred to as secondary particles. After the aqueous polymer dispersion is dried, the polymer primary particles are usually encapsulated in a drying aid shell, as a result of which the primary particles are usually separated from each other; this has the following advantageous effect: the individual primary particles do not undergo irreversible agglomeration. After the polymer powder is redispersed in water, the primary particles are usually released again. Drying aids are also usually present at the interface between the particles and the air, while protective colloids are usually not present.
[0040] Since the water-soluble organic polymer b) used as drying aid is usually added after the polymerization, it is also usually not modified by free-radical initiated polymerization, for example by grafting reactions or by oxidation or reduction reactions of initiators (such as redox initiators), or by hydrolysis (such as the hydrolysis of acetate units by partially hydrolyzed polyvinyl alcohol). As is known, grafting reactions usually attach chemical groups such as monomers to polymers via covalent bonds. Grafting reactions occur to a particularly high extent in the polymerization of vinyl acetate and / or ethylene. On the other hand, protective colloids are usually able to undergo such modifications due to their presence during the polymerization.
[0041] During the polymerization process, polymerization aids or additives such as initiators are likewise directly linked to the polymer chain via covalent bonds or are incorporated into the polymer particles or are encapsulated by the polymer.
[0042] The polymer of ethylenically unsaturated monomers (base polymer) is based, for example, on one or more monomers selected from the group consisting of vinyl esters, (meth)acrylates, vinylaromatics, olefins, 1,3-dienes, and vinyl halides.
[0043] Suitable vinyl esters are, for example, those of carboxylic acids having 1 to 15 carbon atoms. Preference is given to vinyl acetate, vinyl propionate, vinyl butyrate, vinyl 2-ethylhexanoate, vinyl laurate, 1-methylvinyl acetate, vinyl pivalate, and vinyl esters of α-branched monocarboxylic acids having 9 to 11 carbon atoms, such as VeoVa 9R or VeoVa 10R (trade names of Resolution). Particular preference is given to vinyl acetate.
[0044] Suitable monomers from the group of acrylates or methacrylates are, for example, esters of unbranched or branched alcohols having 1 to 15 carbon atoms. Preferred methacrylates or acrylates are methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, and 2-ethylhexyl acrylate. Particular preference is given to methyl acrylate, methyl methacrylate, n-butyl acrylate, tert-butyl acrylate, and 2-ethylhexyl acrylate.
[0045] Preferred vinyl aromatic hydrocarbons are styrene, methylstyrene and vinyltoluene. Preferred vinyl halides are vinyl chloride. Preferred olefins are ethylene and propylene, and preferred dienes are 1,3-butadiene and isoprene.
[0046] Optionally, 0 to 10% by weight, preferably 0.1 to 5% by weight, of auxiliary monomers, based on the total weight of the monomers, can also be copolymerized. Examples of auxiliary monomers are ethylenically unsaturated mono- and dicarboxylic acids, preferably acrylic acid, methacrylic acid, fumaric acid and maleic acid; ethylenically unsaturated carboxamides and nitriles, preferably acrylamide and acrylonitrile; mono- and diesters of fumaric acid and maleic acid, such as diethyl and diisopropyl esters, and maleic anhydride; ethylenically unsaturated sulfonic acids or their salts, preferably vinylsulfonic acid and 2-acrylamido-2-methylpropanesulfonic acid. Further examples are pre-crosslinking comonomers, such as polyethylenically unsaturated comonomers, for example diallyl phthalate, divinyl adipate, diallyl maleate, allyl methacrylate or triallyl cyanurate, or post-crosslinking comonomers, such as acrylamidoglycolic acid (AGA), methyl methacrylamidoglycolate (MAGME), N-methylolacrylamide (NMA), N-methylolmethacrylamide, N-methylolallylcarbamate and alkyl ethers, such as isobutoxy ether or esters of N-methylolacrylamide, N-methylolmethacrylamide and N-methylolallylcarbamate. Also suitable are epoxy-functional comonomers, such as glycidyl methacrylate and glycidyl acrylate. Further examples are silicon-functionalized comonomers such as acryloxypropyltri(alkoxy)- and methacryloxypropyltri(alkoxy)silanes, vinyltrialkoxysilanes, and vinylmethyldialkoxysilanes, where the alkoxy groups present may be, for example, ethoxy and ethoxypropylene glycol ether groups. These also include monomers with hydroxyl or CO groups, such as hydroxyalkyl methacrylates and hydroxyalkyl acrylates, such as hydroxyethyl, hydroxypropyl or hydroxybutyl acrylic acid or methacrylic acid, and compounds such as diacetoneacrylamide and acetoacetoxyethyl acrylic acid or methacrylic acid.
[0047] In an alternative preferred embodiment, no ethylenically unsaturated mono- and dicarboxylic acids, no mono- and diesters of fumaric acid and maleic acid, no maleic anhydride and / or no ethylenically unsaturated sulfonic acids are incorporated into the copolymer by polymerization. Particularly preferably, no auxiliary monomers are incorporated into the copolymer by polymerization.
[0048] Styrene-(meth)acrylate copolymers and especially vinyl acetate-ethylene copolymers are preferred.
[0049] The polymer powder preferably comprises 50 to 90% by weight of the vinyl acetate-ethylene copolymer and / or the styrene-(meth)acrylate copolymer, based on the total weight of the polymer powder.
[0050] Preference is given to copolymers of vinyl acetate with 1 to 50% by weight of ethylene, copolymers of vinyl acetate with 1 to 50% by weight of ethylene and 1 to 50% by weight of one or more further comonomers from the group of vinyl esters having 1 to 12 carbon atoms in the carboxyl group, such as vinyl propionate, vinyl laurate, vinyl esters of α-branched carboxylic acids having 9 to 13 carbon atoms (such as VeoVa 9, VeoVa 10, VeoVa 11); vinyl acetate, 1 to 50% by weight of ethylene and preferably 1 to 60% by weight of (meth)acrylic esters of unbranched or branched alcohols having 1 to 15 carbon atoms, in particular n-butyl acrylate or acrylic acid. and copolymers with 30 to 75% by weight of vinyl acetate, 1 to 30% by weight of vinyl laurate or of vinyl esters of α-branched carboxylic acids having 9 to 11 carbon atoms and 1 to 30% by weight of (meth)acrylic esters of unbranched or branched alcohols having 1 to 15 carbon atoms, in particular n-butyl acrylate or 2-ethylhexyl acrylate, the copolymers also comprising 1 to 40% by weight of ethylene; copolymers with vinyl acetate, 1 to 50% by weight of ethylene and 1 to 60% by weight of vinyl chloride; wherein the polymers may also comprise the auxiliary monomers mentioned in the amounts mentioned, and wherein the figures in % by weight in each case add up to 100% by weight.
[0051] Preference is also given to (meth)acrylate polymers, such as copolymers of n-butyl acrylate or 2-ethylhexyl acrylate, or copolymers of methyl methacrylate with n-butyl acrylate and / or 2-ethylhexyl acrylate; styrene-acrylate copolymers with one or more monomers from the group of methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate and 2-ethylhexyl acrylate; vinyl acetate-acrylate copolymers with one or more monomers from the group of methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate and, optionally, ethylene; styrene-1,3-butadiene copolymers; wherein the polymers may also comprise the auxiliary monomers mentioned in the amounts mentioned, and wherein the figures in % by weight in each case add up to 100 % by weight.
[0052] Most preferred are copolymers with vinyl acetate and 5 to 50% by weight of ethylene; or copolymers with vinyl acetate, 1 to 50% by weight of ethylene and 1 to 50% by weight of vinyl esters of α-branched monocarboxylic acids having 9 to 11 carbon atoms; or copolymers with 30 to 75% by weight of vinyl acetate, 1 to 30% by weight of vinyl laurate or vinyl esters of α-branched carboxylic acids having 9 to 11 carbon atoms and 1 to 30% by weight of (meth)acrylic esters of unbranched or branched alcohols having 1 to 15 carbon atoms, the copolymers also containing 1 to 40% by weight of ethylene; or copolymers with vinyl acetate, 5 to 50% by weight of ethylene and 1 to 60% by weight of vinyl chloride.
[0053] The proportions by weight of the monomers and comonomers are selected so that the glass transition temperature Tg is preferably -50°C to +35°C, more preferably -30°C to +25°C and most preferably -10°C to +20°C. The glass transition temperature Tg of the polymer can be determined in a known manner by differential scanning calorimetry (DSC). Tg can also be approximately predicted by the Fox equation. According to Fox T.G., Bull. Am. Physics Soc. 1, 3, 123 pages (1956): 1 / Tg=x1 / Tg1+x2 / Tg2+...+xn / Tgn, where xn is the mass fraction of monomer n (% by weight / 100), and Tgn is the glass transition temperature of the homopolymer of monomer n in Kelvin. The Tg values of homopolymers are listed in Polymer Handbook 2nd Edition, J. Wiley & Sons, New York (1975).
[0054] The polymers are preferably obtainable by emulsion polymerization or suspension polymerization of one or more ethylenically unsaturated monomers in an aqueous medium. The polymers are preferably produced by an emulsion polymerization process.
[0055] The polymerization temperature is preferably between 40 and 110° C., more preferably between 60 and 90° C. In the copolymerization of gaseous comonomers such as ethylene, 1,3-butadiene or vinyl chloride, it is also possible to work at pressures of typically between 5 and 100 bar.
[0056] The polymerization is initiated using a water-soluble or monomer-soluble initiator or a redox initiator combination that is commonly used for emulsion polymerization or suspension polymerization. Examples of water-soluble initiators are sodium, potassium and ammonium salts of peroxodisulfuric acid, hydrogen peroxide, tert-butyl peroxide, tert-butyl hydroperoxide, potassium peroxydiphosphate, tert-butyl peroxypivalate, cumene hydroperoxide, isopropylbenzene monohydroperoxide, and azobisisobutyronitrile. Examples of monomer-soluble initiators are dihexadecyl peroxydicarbonate, dicyclohexyl peroxydicarbonate and dibenzoyl peroxide. The mentioned initiators are usually used in an amount of 0.01% to 1.0% by weight, preferably 0.0015% to 0.7% by weight, more preferably 0.002% to 0.4% by weight and most preferably 0.0025% to 0.3% by weight, in each case based on the total weight of the monomers.
[0057] The redox initiators used are combinations of the initiators mentioned and of reducing agents. Suitable reducing agents are alkali metal and ammonium sulfites and bisulfites, for example sodium sulfite; derivatives of sulfoxylic acid such as zinc or alkali metal formaldehyde sulfoxylate, for example sodium hydroxymethanesulfinate; and ascorbic acid. The amount of reducing agent is generally 0.001% to 1.0% by weight, preferably 0.0015% to 0.7% by weight, more preferably 0.002% to 0.4% by weight and most preferably 0.0025% to 0.3% by weight, in each case based on the total weight of the monomers.
[0058] Substances that act as chain transfer agents can be used during the polymerization to control the molecular weight. When chain transfer agents are used, they are generally used in amounts of 0.01 to 5.0% by weight, based on the monomers to be polymerized, and are metered in separately or in the form of a premix with the reaction components. Examples of such substances are n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptopropionic acid, methyl mercaptopropionate, isopropanol, and acetaldehyde.
[0059] Suitable protective colloids for the polymerization are the same as for the water-soluble organic polymers b) and are correspondingly the preferred polymers described above. Preference is therefore given to polyvinyl alcohol.
[0060] The protective colloid is added in the polymerization in an amount of preferably 1 to 20% by weight, more preferably 2 to 15% by weight, and most preferably 3 to 10% by weight, based on the total weight of the monomers.
[0061] If the polymerization is carried out in the presence of an emulsifier, its amount is 0.5 to 5% by weight, based on the amount of monomers. Suitable emulsifiers are anionic, cationic and nonionic emulsifiers, for example anionic surfactants such as alkyl sulfates having a chain length of 8 to 18 carbon atoms, alkyl or alkylaryl ether sulfates having 8 to 18 carbon atoms in the hydrophobic group and having up to 40 ethylene oxide or propylene oxide units, alkyl sulfonates or alkylaryl sulfonates having 8 to 18 carbon atoms, esters and monoesters of sulfosuccinic acid with monohydric alcohols or alkylphenols; or nonionic surfactants such as alkyl polyglycol ethers or alkylaryl polyglycol ethers having 8 to 40 ethylene oxide units.
[0062] The polymerization is particularly preferably carried out in the absence of emulsifiers. The aqueous dispersion and / or the polymer powder preferably does not contain any emulsifiers.
[0063] After the polymerization is complete, residual monomers can be removed by post-polymerization using known methods, usually by post-polymerization initiated by a redox catalyst. Volatile residual monomers can also be removed by distillation (preferably under reduced pressure) and optionally while passing an inert entraining gas (such as air, nitrogen or water vapor) through or over.
[0064] The polymers thus obtained are preferably in the form of aqueous dispersions, especially protective colloid-stabilized aqueous dispersions.
[0065] The addition of the inorganic salts a) used as drying aids can be carried out before, during or preferably after the production of the polymer by polymerization. It is also possible to use chemical substances which are converted into the inorganic salts a) according to the invention by chemical reactions.
[0066] For example, the inorganic salt a) may be mixed with the ethylenically unsaturated monomers before initiating the polymerization. Alternatively, the inorganic salt a) may be added during the polymerization of the ethylenically unsaturated monomers. Similarly, a portion of the inorganic salt a) may be mixed with the ethylenically unsaturated monomers before initiating the polymerization, and the remaining portion of the inorganic salt a) may be added during the polymerization of the ethylenically unsaturated monomers.
[0067] Preferably, the inorganic salt a) is added to the corresponding polymer dispersion at the end of the polymerization. More preferably, the addition of the inorganic salt a) is carried out before the drying of the aqueous polymer dispersion. For this purpose, preferably one or more inorganic salts a) are added to the aqueous polymer dispersion in order to subsequently dry the resulting mixture. During the drying of the aqueous polymer dispersion, preferably no inorganic salt a) is added.
[0068] Any water-soluble organic polymer b) used as drying aid is generally added to the polymer dispersion, for example spatially or temporally together with the inorganic salt a) or separately therefrom.
[0069] The polymer dispersion can be dried, for example, by fluidized bed drying, freeze drying or spray drying. The dispersion is preferably spray dried. Spray drying is carried out in a standard spray drying system, wherein atomization can be carried out by a single, two or multiphase nozzle or with a rotating disk. Depending on the system, the Tg of the resin, and the desired degree of drying, the selected outlet temperature is generally in the range of 45°C to 120°C, preferably 60°C to 90°C. The viscosity of the feed to be atomized is set by the solid content so that a value of preferably <10000 mPa·s, more preferably <5000 mPa·s, and particularly preferably <1000 mPa·s (Brookfield viscosity at 20 revolutions and 23°C) is obtained. The solid content of the dispersion to be atomized is preferably from 30% to 75% by weight and more preferably from 50% to 60% by weight.
[0070] Contents of up to 1.5% by weight of defoamers, based on the polymer, have proven to be advantageous in many cases. The defoamers are preferably added during atomization.
[0071] In order to improve storage stability by improving caking stability, especially in the case of polymer powders with low glass transition temperatures, one or more anti-caking agents (anti-caking agents) can be provided for example for the polymer powder obtained. The anti-caking agent is preferably not added to the aqueous polymer dispersion, i.e., preferably not before drying, but preferably during or after drying, especially during drying in a spray drying system. Preferred polymer powders include an anti-caking agent, especially 1% to 30% by weight based on the total weight of the polymer components. Examples of anti-caking agents are calcium carbonate or magnesium carbonate, talc, gypsum, silicon dioxide, kaolin such as metakaolin, and silicates, preferably with a particle size in the range of 10 nm to 10 μm. Anti-caking agents are generally water-insoluble.
[0072] In order to improve the performance properties, further additives can be added during drying. Further constituents of the polymer powder present in a preferred embodiment are, for example, pigments, fillers, foam stabilizers, hydrophobizing agents or cement plasticizers.
[0073] The polymer powder preferably does not contain any polyelectrolytes. A polyelectrolyte generally refers to a polymer having groups that can dissociate into ions in an aqueous medium and that can be a component or substituent of a polymer chain. The number of groups that can dissociate into ions is generally large enough to render the polymer in a dissociated form that is completely soluble in water. A polyelectrolyte can be, for example, a polyacid or a polybase.
[0074] The polymer powder preferably contains no water-soluble halide salts, in particular no water-soluble chloride salts. Water-soluble halide salts have a water solubility of preferably ≥ 1 g / liter of water under standard conditions (23 / 50) according to DIN 50014.
[0075] The polymer powder preferably contains no polyfunctional alcohols, in particular no alcohols with at least one alcohol group and optionally one or more further functional groups selected from the group consisting of amine, carbamic acid, thiol, sulfonic acid, sulfuric acid, halogen, carboxyl, alkoxy, phosphinic acid, phosphonic acid, and phosphoric acid groups, wherein the sum of the number of alcohol groups and further functional groups of the alcohol is ≥ 2. The polymer powder preferably contains no alcohols with ≤ 20, more preferably ≤ 15, or > 2 carbon atoms.
[0076] The polymer powder is preferably free of polyalkylene polyamines, in particular free of polyethyleneimine, in particular free of polyethyleneimine having a molecular weight of 300 to 10 000 000. Polyalkylene polyamines are generally based on ethylenically unsaturated monomers carrying amine, ammonium or amide groups and optionally further ethylenically unsaturated monomers.
[0077] Preferably, no salts of polyvalent metals are added to the polymer dispersion, in particular no salts of magnesium, calcium, barium, aluminum, zirconium, iron or zinc.
[0078] The invention further provides dry formulations for building materials comprising one or more hydraulic binders, one or more fillers, one or more polymer powders according to the invention and optionally one or more additives.
[0079] The dry building material formulation preferably comprises 0.1 to 30% by weight, more preferably 0.3 to 12.0% by weight and most preferably 0.5 to 5.0% by weight of the polymer powder of the invention, based in each case on the total weight of the dry building material formulation.
[0080] Examples of suitable hydraulic binders are cements, in particular Portland cement, aluminate cement, pozzolanic cement, slag cement, magnesia cement, phosphate cement or blast furnace cement, and also blended cements, filler cements, fly ash, microsilica, hydraulic lime and gypsum. Preference is given to Portland cement, aluminate cement and slag cement and also blended cement, filler cement, hydraulic lime and gypsum. Preference is also given to mixtures of two or more hydraulic binders, in particular comprising cement and hydraulic lime.
[0081] Typically, the dry building material formulation comprises 5 to 50% by weight, preferably 10 to 30% by weight, of hydraulic binder, based in each case on the total weight of the dry building material formulation.
[0082] Examples of suitable fillers are quartz sand, quartz powder, calcium carbonate, dolomite, aluminum silicate, clay, chalk, white slaked lime, talcum powder or mica, or also lightweight fillers such as pumice, foam glass, aerated concrete, perlite, vermiculite and carbon nanotubes (CNT). Any desired mixture of the fillers can also be used. Preference is given to quartz sand, quartz powder, calcium carbonate, chalk or slaked white lime. The filler is usually / implicitly insoluble in water.
[0083] In general, the dry building material formulations comprise from 30 to 90% by weight, preferably from 40 to 85% by weight, of fillers, based in each case on the total weight of the dry building material formulation.
[0084] Other conventional additives for dry formulations of building materials are thickeners, for example polysaccharides (such as cellulose ethers and modified cellulose ethers), starch ethers, guar gum, xanthan gum, sheet silicates, polycarboxylic acids (such as polyacrylic acid and its partial esters), and also polyvinyl alcohol (which may optionally be acetalized or hydrophobically modified), casein, and associative thickeners. Conventional additives also include retarders, such as hydroxycarboxylic acids or dicarboxylic acids or their salts, sugars, oxalic acid, succinic acid, tartaric acid, gluconic acid, citric acid, sucrose, glucose, fructose, sorbitol and pentaerythritol. Conventional additives are coagulants, for example alkali metal or alkaline earth metal salts of inorganic or organic acids. In addition, the following should also be mentioned: hydrophobic agents, preservatives, film formers, dispersants, foam stabilizers, defoamers, and flame retardants (such as aluminum hydroxide).
[0085] The additives are used in customary amounts, depending on the nature of the additive. Typically, the amounts are from 0.01 to 10% by weight, based in each case on the total weight of the dry formulation of the building material.
[0086] Dry building material formulations are usually produced by mixing and homogenizing one or more hydraulic binders, one or more fillers, one or more polymer powders, and optionally one or more additives to form a dry mixture. The production of dry building material formulations can be carried out in a conventional manner in conventional equipment. The amount of water required for processing the dry building material formulation is usually added immediately before application.
[0087] The building material dry formulation is suitable, for example, for the production of reinforcing compounds for thermal insulation composite systems, or for the production of adhesives or coating materials. Examples of adhesives are adhesives for thermal insulation panels and sound insulation panels, tile adhesives, and adhesives for bonding wood and wood-based materials. Examples of coating materials are mortars, self-leveling compounds, sealing slurries, screeds, and plasters.
[0088] By adding the polymer powder according to the invention to a dry formulation of building materials, surprisingly building products are obtained which have improved tensile adhesion strength after thermal aging. It is particularly surprising here that this is achieved by using alkali metal sulfates or alkali metal sulfites as drying aids, which are not known per se to be able to be used to improve the tensile adhesion strength of building products after thermal aging.
[0089] Advantageously, even with relatively small amounts of the polymer powders of the present invention, the tensile adhesion strength after heat aging can be significantly improved. DETAILED DESCRIPTION
[0090] The following examples are provided to further illustrate the present invention.
[0091] Production of polymer powders:
[0092] The polymer powders were each produced using the same conventional polymer dispersion of a vinyl acetate-ethylene copolymer having a glass transition temperature Tg of 17° C. The polymer dispersion was produced in a conventional manner by emulsion polymerization and contained 6% by weight of polyvinyl alcohol as protective colloid.
[0093] The amounts of drying aid listed in Table 1 were added to this polymer dispersion.
[0094] For all (comparative) examples, the resulting spray feed was dried in a conventional manner itself by spray drying to give a redispersible polymer powder.
[0095] 20% by weight of an anti-caking agent was added to each of the polymer powders thus produced during spray drying.
[0096] The polymer powder was tested in a cementitious tile adhesive having the following formulation:
[0097] Tile Adhesive1 , containing 3% by weight of a polymer powder:
[0098] 420g Milke CEM I
[0099] 460 g of quartz sand with average particle size
[0100] 81 g calcium carbonate
[0101] 4g of Tylose
[0102] 5g of accelerator
[0103] 30 g of the polymer powder of the corresponding (comparative) example
[0104] 310g water
[0105] Tile Adhesive2 , containing 6% by weight of a polymer powder:
[0106] 400g Milke CEM I
[0107] 265.5 g of coarse quartz sand
[0108] 265.5g of fine quartz sand
[0109] 4g of Tylose
[0110] 5g of accelerator
[0111] 60 g of the polymer powder of the corresponding (comparative) example
[0112] 270g water
[0113] Tile adhesive 1 or tile adhesive 2 was applied in a conventional manner. The test of the tensile adhesion value after heat aging was carried out in accordance with EN1348.
[0114] The results of the tests are summarized in Table 1.
[0115] Table 1:
[0116]
[0117]
[0118] a) % by weight (solids / solids), based on the polymer content of the dispersion.
[0119] b) PVOH (04 / 88): with 4 mPas viscosity and 88% degree of hydrolysis of polyvinyl alcohol.
[0120] The test results in Table 1 show that the addition of inorganic salt a) as a drying aid improves the tensile adhesion value after heat aging.
Claims
1. A process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders, The process is carried out by drying an aqueous dispersion of a protective colloid-stabilized polymer based on ethylenically unsaturated monomers in the presence of one or more drying aids, characterized in that The drying aid comprises a) one or more inorganic salts selected from the group consisting of alkali metal sulfates and alkali metal sulfites and b) optionally one or more water-soluble organic polymers, and After addition of all drying aids, the inorganic salt a) is present in dissolved form in the aqueous dispersion of the protective colloid-stabilized polymer based on ethylenically unsaturated monomers, wherein the inorganic salt a) is used as a drying aid in an amount of ≥25% by weight based on the total weight of the drying aid, and Therein, the proportion of any water-soluble organic polymer b) used as drying aid is ≤40% by weight, based on the total weight of the protective colloid and any water-soluble organic polymer b) used as drying aid.
2. Process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders according to claim 1, characterized in that From 0.1 to 20% by weight of inorganic salt a) is used, based on the total weight of the polymer, which is based on ethylenically unsaturated monomers.
3. Process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders according to claim 1 or 2, characterized in that 2 to 50% by weight of inorganic salt a) are used, based on the total weight of the protective colloid.
4. Process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders according to claims 1 to 3, characterized in that 2 to 50% by weight of inorganic salt a) are used, based on the total weight of the protective colloid and the water-soluble organic polymer b).
5. Process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders according to claims 1 to 4, characterized in that Sodium sulfate, sodium sulfite, potassium sulfate and / or potassium sulfite are used as inorganic salts a).
6. Process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders according to claims 1 to 5, characterized in that The one or more water-soluble organic polymers b) are selected from the group consisting of polyvinyl alcohol, polyvinyl acetal, nonionic polyvinyl pyrrolidone, nonionic poly(meth)acrylamide, polysaccharides and proteins.
7. Process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders according to claims 1 to 6, characterized in that Exclusively inorganic salts a) are used as drying aids.
8. Process for producing protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of water-redispersible powders according to claims 1 to 6, characterized in that producing an aqueous dispersion of the protective colloid-stabilized polymer based on ethylenically unsaturated monomers by polymerizing one or more ethylenically unsaturated monomers in an aqueous medium, wherein the protective colloid is added before or during the polymerization, and After the production of the aqueous dispersion by polymerization, any water-soluble organic polymer b) used as drying aid is added to the aqueous dispersion of the protective colloid-stabilized polymer.
9. A protective colloid-stabilized polymer based on ethylenically unsaturated monomers in the form of a water-redispersible powder, obtainable by a process as claimed in claims 1 to 8.
10. A dry formulation for a building material comprising one or more hydraulic binders, one or more fillers, one or more protective colloid-stabilized polymers based on ethylenically unsaturated monomers in the form of a water-redispersible powder from claim 9, and optionally one or more additives.
11. Use of the dry building material formulation according to claim 10 for producing reinforcing compounds for thermal insulation composite systems or for producing adhesives or coating materials.
Citation Information
Patent Citations
Process for preparing non blocking, in water readily dispersible polymer powders by spraying aqueous polymer dispersions
EP0078449A2
Process for preparing redispersable powder based on dispersions stabilised with natural substances as protective colloids
EP0134451A2
Polymer powder redispersable in water, obtainable by spraying aqueous polymer dispersions and its application as additive in hydraulic binders
EP0407889A1
Redispersion powder composition with a binding acceleration effect
US20070037925A1
Redispersible dispersion powder composition
US5567750A